2013
DOI: 10.1155/2013/529087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Technology Integrated and Nonintegrated Arterial Filters Used in Cardiopulmonary Bypass Surgery: A Randomized, Prospective, and Single Blind Study

Abstract: Background. Innovative cardiopulmonary bypass (CPB) settings have been developed in order to integrate the concepts of “surface-coating,” “blood-filtration,” and “miniaturization.” Objectives. To compare integrated and nonintegrated arterial line filters in terms of peri- and postoperative clinical variables, inflammatory response, and transfusion needs. Material and Methods. Thirty-six patients who underwent coronary bypass surgery were randomized into integrated (Group In) and nonintegrated arterial line fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The design of the newer oxygenators also allows incorporation of the arterial filter within the oxygenator chamber. [9,17] On the other hand, studies comparing conventional oxygenators without integrated arterial filters to those newer oxygenators with integrated arterial filters aiming at minimizing the risk of micro-embolism and POCD by forming less micro-bubbles and by entrapping more microbubbles are relatively low in number. To the best of our knowledge, the present study is the first prospective, randomized study to compare these two CPB oxygenator systems in terms of their effects on neurocognitive functions and neuroradiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the newer oxygenators also allows incorporation of the arterial filter within the oxygenator chamber. [9,17] On the other hand, studies comparing conventional oxygenators without integrated arterial filters to those newer oxygenators with integrated arterial filters aiming at minimizing the risk of micro-embolism and POCD by forming less micro-bubbles and by entrapping more microbubbles are relatively low in number. To the best of our knowledge, the present study is the first prospective, randomized study to compare these two CPB oxygenator systems in terms of their effects on neurocognitive functions and neuroradiological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study by Gursu et al, [9] Sorin Synthesis integrated arterial filtration system was compared with Sorin Dideco Compactflo (Dideco Compactflo Evo, Sorin group, Mirandola Modena, Italy) non-integrated arterial filtration system in patients undergoing CABG with respect to certain clinical variables, inflammatory responses, and need for transfusion. The authors did not report data on the incidence of embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[14][15][16][17][18] Although the best performing system in terms of emboli handling was a non-integrated system, we did not demonstrate a systematic disadvantage for integrated systems per se and the potential for them to have other advantages must be acknowledged. For example, Gursu et al 19 compared clinical variables, inflammatory responses and transfusion needs in thirty-six patients who underwent coronary artery surgery randomised to CPB using either a Sorin Synthesis integrated filtration system or the Sorin Dideco Compactflo oxygenator plus a separate ALF. Emboli data were not reported in this comparison.…”
Section: Discussionmentioning
confidence: 99%
“…A major part (n=11) of these focused on the effects of leukocyte filters, 33,34 dynamic bubble traps [35][36][37] or comparing different modes of arterial line filtration. 26,28,[38][39][40][41] Only four (n=4) RCT were specifically designed to investigate the effects of arterial line filters (Table 3); 14,[42][43][44] one study group using ALF was compared to a control group without any type of filtration device. 14 The main result indicated that the use of ALF protects the brain, verified by Doppler measurements and cognitive test results.…”
Section: Review Of Randomised Clinical Trialsmentioning
confidence: 99%